"Ultraslow wave nuclear burning of uranium–plutonium fissile medium on epithermal neutrons" by V.D. Rusov et al. (April 2023) - van Rooijen, W.F.G.
Highlights: The published paper by Rusov et al. contains several fundamental errors. The work is based on physically impossible assumptions and has wrong conclusions. Simulations of Rusov et al. are based on an incorrect depletion chain. There is no "nuclear burning wave" in the work of Rusov et al.